Ficciones que se bifurcan. La presencia de Borges en Cien años de soledad. - (:unkn) unknown (Syracuse University, 2012)
his article explores the presence of Jorge Luis Borges's texts in Gabriel García Márquez's Cien años de soledad. It begins with a discussion of some of the critical essays that analyze commonalities between Borges's works and García Márquez's novel. It then focuses on the textual analysis and meaning of four topics, considered recurrent themes in Borges's texts, that are used by Marquez: 1) the fantastic invention of an “Aleph” (a kind of magical lens through which everything around the world can be seen in an instant); 2) the search for a totalizing language; 3) memory, oblivion, and their relations with the creation of languages; and 4) dreams and insomnia as paths to analyze notions such as the infinite, repetitions, and death.

Cita del artículo: “La presencia de Borges en Cien años de soledad.” Symposium: A Quarterly Journal in Modern Literatures. 66.1 (2012): 1-14.
Keywords: Borges, Cien años de soledad, García Márquez